Feasibility Analysis of Kekar Tilapia Farming in South Konawe Regency - Musadar, Musadar; Muthalib, Abd Aziz; Nuryadi, Ahmad Muhlis; Murniati, Murniati; Hartono, Yudhi Dwi (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2021)
The fisheries sector plays a vital role in developing and providing business and employment opportunities to support the community and regional economy. Kekar tilapia is one of the freshwater fish farming commodities in the fisheries business sector and relatively new tilapia variety with the advantages of a thick (stocky) and a more comprehensive body shape with a smaller head than others tilapia. This case study aimed to determine the income and feasibility of kekar tilapia farming in the South Konawe Regency, explicitly studying the UKM Empang Sari (Small and Medium Enterprise/SME of Empang Sari). Research variables included cost components (fixed and variable costs) and revenue components (production and selling price). The data were analyzed using income and business feasibility analyses. The study results reveal that tilapia fish farming in South Konawe Regency is profitable and feasible, with IDR 4.355.000 per production cycle or IDR 13.066.000 per year with an R/C ratio of 1.6. Hence, it is suggested that UKM Empang Sari increase the kekar tilapia cultivation.